Hyperauthorship: A comparative study of genetics and high-energy physics research - Changa, Yu-Wei; Huang, Mu-Hsuan; Chiu, Min-Jy (Malaysian Journal of Library and Information Science, 2019)
The number of hyperauthored articles has increased in certain disciplines; yet, little research has been conducted on hyperauthorship. Because genetics and high-energy physics are fields that exhibit hyperauthorship, this study focused on the differences and trends in the characteristics and influence of hyperauthored articles in these fields, for which articles published between 2004 and 2013 were used. The findings show that the percentage of hyperauthored articles in high-energy physics was higher than that of those in genetics. Although low small proportions of hyperauthored articles were identified in the two fields, increasing trends were observed in the annual percentages of hyperauthored articles. The average numbers of authors, institutions, and countries per hyperauthored article in high-energy physics were higher than those in genetics. Furthermore, increasing trends were identified in the annual average numbers of authors and institutions per hyperauthored article in both fields. The average numbers of citations received by hyperauthored articles were significantly greater than those of other coauthored articles in both fields. A higher percentage of hyperauthored articles in high-energy physics received more than 100 citations than did multiauthored articles. A similar phenomenon did not occur in genetics.